Phonological architecture a biolinguistic approach - Samuels, Bridget D. (Oxford : Oxford University Press, 2011)
'Phonological Architecture' bridges linguistic theory and the biological sciences, presenting a comprehensive view of phonology from a biological perspective. Its back-to-basics approach breaks phonology into primitive operations and representations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Biolinguistics; Phonetics